The Role of Mitonuclear Incompatibility in Bipolar Disorder Susceptibility and Resilience Against Environmental Stressors - Gonzalez, Suzanne (Frontiers in Genetics, 2021)
It has been postulated that mitochondrial dysfunction has a significant role in the underlying pathophysiology of bipolar disorder (BD). Mitochondrial functioning plays an important role in regulating synaptic transmission, brain function, and cognition. Neuronal activity is energy dependent and neurons are particularly sensitive to changes in bioenergetic fluctuations, suggesting that mitochondria regulate fundamental aspects of brain function. Vigorous evidence supports the role of mitochondrial dysfunction in the etiology of BD, including dysregulated oxidative phosphorylation, general decrease of energy, altered brain bioenergetics, co-morbidity with mitochondrial disorders, and association with genetic variants in mitochondrial DNA (mtDNA) or nuclear-encoded mitochondrial genes. Despite these advances, the underlying etiology of mitochondrial dysfunction in BD is unclear. A plausible evolutionary explanation is that mitochondrial-nuclear (mitonuclear) incompatibility leads to a desynchronization of machinery required for efficient electron transport and cellular energy production. Approximately 1,200 genes, encoded from both nuclear and mitochondrial genomes, are essential for mitochondrial function. Studies suggest that mitochondrial and nuclear genomes co-evolve, and the coordinated expression of these interacting gene products are essential for optimal organism function. Incompatibilities between mtDNA and nuclear-encoded mitochondrial genes results in inefficiency in electron flow down the respiratory chain, differential oxidative phosphorylation efficiency, increased release of free radicals, altered intracellular Ca2+ signaling, and reduction of catalytic sites and ATP production. This review explores the role of mitonuclear incompatibility in BD susceptibility and resilience against environmental stressors.